A place in the country - Adler, Elizabeth (Elizabeth A.) (St. Martin's Press, 2012)
Newly-single mother Caroline Evans dreams of restoring an old barn into a restaurant, but her chance at happiness suddenly hangs in the balance as whispers of murder and vengeance find their way to her and her daughter Issy, hovering in that limbo between girl and young woman, begins to make some dangerous choices.